Antagonism activity of phosphate solubilizing microbes and nitrogen fixing bacteria toward Fusarium sp. - Fitriatin, Betty Natalie; Dewi, Yeni Wispa; Sofyan, Emma Trinurani (International Journal of Environment, Agriculture and Biotechnology, 2020)
The ability of phosphate solubilizing microbes and N-fixing bacteria as biofertilizers to increase growth and soil P-dissolve, N soil, they also have the potential to suppress disease, The purpose of this experiment to study antagonism activity of phosphate solubilizing microbes and N-fixing bacteria to inhibit pathogen isolate. In vitro antagonism test was carried out to test the ability of isolates biofertilizers as biocontrol The isolate of phosphate solubilizing microbes were Pseudomonas mallei, Pseudomonas cepacea, Bacilkussubtilis, Bacillus megaterium, Penicilliumsp.,and Aspergillusniger while the isolate ofN-fixing bacteria were (Azotobactervinelandii, Azotobacterchroococcum and Azospirillumsp. Fusarium sp. as pathogen was used for antagonism test. The experiment showed that phosphate solubilizing microbes and N-fixing bacteria have ability to inhibit growth of Fusariumsp. as pathogen. The results of the antagonism test of the biofertilizer isolates tested by Azospirillum were able to inhibit the growth of Fusariumsp. higher than other isolates.Furthermore, from this study it can be developed that biofertilizers are not only to increase soil nutrient availability and plant growth but can be used as biocontrol.